Публічність і самостійність самоврядної (муніципальної) влади - Григор'єв, В.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
This article is dedicated to the issues of publicity and independence of the self-administrative (municipal) power in Ukraine. The recognition and legalisation of the public self-administrative power in Ukraine, remarks the author, is contained in article 7 of the Constitution of Ukraine which recognises and guarantees local government. The self-administrative power is generated and «stems» from the state power, exists under its positive protectionism, and, in its turn, strengthens and stabilises the state power. The self-administrative power and the state power, concludes the author, are subsystems of the public power and they are completely independent and equal in their rights.